2020
DOI: 10.1029/2019wr025750
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Freshwater Lenses Adjacent to Gaining Rivers Through Vertical Low‐Hydraulic‐Conductivity Barriers: Analytical and Experimental Validation

Abstract: Freshwater lenses within riparian zones of some arid and semiarid settings assist in maintaining the health of riparian ecosystems. We propose an approach for expanding freshwater lenses in saline aquifers adjacent to gaining rivers through the addition of a vertical barrier of low‐hydraulic‐conductivity (low‐K) parallel to the river bank. Sharp‐interface analytical solutions for the lens shape and water table distribution are developed to examine the effectiveness of the proposed method and are verified using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Recently, Wu et al. (2020) adapted the analytical method of Werner and Laattoe (2016) to derive analytical solutions for the effect on riparian lenses of adding a vertical, low‐hydraulic‐conductivity barrier, aimed at increasing lens size. They verified their solution using laboratory sand tank experiments and showed that riparian lenses are expanded when a barrier is added only if the situation of the aquifer at its inland extent represents a constant‐head condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wu et al. (2020) adapted the analytical method of Werner and Laattoe (2016) to derive analytical solutions for the effect on riparian lenses of adding a vertical, low‐hydraulic‐conductivity barrier, aimed at increasing lens size. They verified their solution using laboratory sand tank experiments and showed that riparian lenses are expanded when a barrier is added only if the situation of the aquifer at its inland extent represents a constant‐head condition.…”
Section: Introductionmentioning
confidence: 99%
“…A correction to account for the lack of freshwater-saltwater mixing in the sharp-interface solutions of was developed by Werner (2017), who explored the groundwater age within riparian lenses using numerical simulation and linked this to the circulation of freshwater caused by dispersive mixing. Recently, Wu et al (2020) adapted the analytical method of to derive analytical solutions for the effect on riparian lenses of adding a vertical, low-hydraulic-conductivity barrier, aimed at increasing lens size. They verified their solution using laboratory sand tank experiments and showed that riparian lenses are expanded when a barrier is added only if the situation of the aquifer at its inland extent represents a constant-head condition.…”
mentioning
confidence: 99%
“…Laboratory‐scale sand tanks are commonly employed to investigate variable‐density flow problems, which are usually challenging to characterize under field conditions. For example, laboratory experiments have been utilized in previous studies of riparian lenses (e.g., Jazayeri et al., 2021; Werner et al., 2016; Wu et al., 2020), freshwater lenses in oceanic islands (e.g., Lu et al., 2019; Stoeckl et al., 2016) and the transience of seawater intrusion and retreat in coastal aquifers (e.g., Abdoulhalik & Ahmed, 2018; Badaruddin et al., 2015; Goswami & Clement, 2007). In addition, physical experiments can provide benchmark data to assess the performance of numerical models, particularly where buoyancy forces and dispersion lead to complex transport processes (e.g., Goswami & Clement, 2007; Oswald & Kinzelbach, 2004; Werner et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that where the thickness of the unsaturated zone is small, floodplain evaporation may play a dominant role in controlling the freshwater-saltwater distribution, leading to hypersaline groundwater and freshwater bodies that lack the lenticular shape expected in the absence of evaporation. Wu et al (2020) proposed an approach for expanding riparian lenses by adding a vertical low-hydraulic-conductivity barrier parallel to the riverbank. They developed a sharp-interface analytical solution to examine the effectiveness of their proposed approach and validated the analytical solution using sand tank experiments and numerical simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation